2019
DOI: 10.1108/ec-07-2018-0298
|View full text |Cite
|
Sign up to set email alerts
|

The multi-objective optimization of a non-pneumatic wheel based on its life prediction

Abstract: Purpose A novel non-pneumatic safety tire, namely mechanical elastic wheel (ME-Wheel), has been developed recently to solve problems, including tire bursting and flat tire, of typical pneumatic tires. This paper aims to predict the life of the ME-Wheel accurately and settle the problem of lower lifespan. Design/methodology/approach This study proposes a new method to establish a novel model of virtual proving ground based on finite element analysis, and by combining with the random vibration damage analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Qi et al 21 found that the relatively appropriate honeycomb support density can overall stress level of the tire is low, which can effectively avoid damage due to stress concentration. Xiao et al 22,23 proposed a method to predict the fatigue life of mechanical elastic tire by using finite element life design, and verified the theoretical calculation and simulation results through experiments. At the same time, a new virtual test site model based on finite element analysis is proposed.…”
Section: Introductionmentioning
confidence: 93%
“…Qi et al 21 found that the relatively appropriate honeycomb support density can overall stress level of the tire is low, which can effectively avoid damage due to stress concentration. Xiao et al 22,23 proposed a method to predict the fatigue life of mechanical elastic tire by using finite element life design, and verified the theoretical calculation and simulation results through experiments. At the same time, a new virtual test site model based on finite element analysis is proposed.…”
Section: Introductionmentioning
confidence: 93%
“…Studying the influence of pavement inclination angle on the stress distribution of honeycomb-based tires, Sriwijaya and Hamzah 95 showed that with the increase in inclination angle comes an increase in stress along the internal structure of the tire, thus diminishing the life expectancy of the NPT. Using a finite element life design-based methodology, Xiao et al 89,106 proposed a method to predict the fatigue life of elastic tires which, combined with a random vibration damage analysis method, accurately predicted the life of the NPT under study.…”
Section: Mechanical Behaviour Of Nptsmentioning
confidence: 99%
“…The basic assumption of the adaptive learning rate is that the learning rate can be adjusted adaptively according to the error change. The learning rate adaptive mechanism used in the training is shown in equation (14).…”
Section: Algorithm Improvementmentioning
confidence: 99%
“…Zhao et al 13 investigated the ME wheel with different hinge structure and distribution, and compared the stiffness properties of ME wheel with those of an inflatable tire. Based on the technology of virtual proving ground, Xiao et al 14 analyzed and predicted the service life of the ME wheel, and carried out multi-objective optimization design.…”
Section: Introductionmentioning
confidence: 99%